Potential of Methylglyoxal-Conjugated Chitosan Nanoparticles in Treatment of Fluconazole-Resistant Candida albicans Infection in a Murine Model - Khan SH; Younus H; Allemailem KS; Almatroudi A; Alrumaihi F; Alruwetei AM; Alsahli MA; Khan A; Khan MA (International Journal of Nanomedicine, 2020)
Shaheer Hasan Khan,1,* Hina Younus,1,* Khaled S Allemailem,2 Ahmad Almatroudi,2 Faris Alrumaihi,2 Abdulmohsen M Alruwetei,2 Mohammed A Alsahli,2 Arif Khan,3 Masood Alam Khan3 1Interdisciplinary Biotechnology Unit, Aligarh Muslim University, Aligarh 202002, India; 2Department of Medical Laboratories, College of Applied Medical Sciences, Qassim University, Buraidah 51452, Saudi Arabia; 3Department of Basic Health Sciences, College of Applied Medical Sciences, Qassim University, Buraidah, 51452, Saudi Arabia*These authors contributed equally to this workCorrespondence: Masood Alam KhanDepartment of Basic Health Sciences, College of Applied Medical Sciences, Qassim University, Buraydah, KSA 51452 Tel +966-507059437Fax +966-63801628Email a_khan@qu.edu.saBackground: Fungal infections are becoming more prevalent and threatening because of the continuous emergence of azole-resistant fungal infections. The present study was aimed to assess the activity of free Methylglyoxal (MG) or MG-conjugated chitosan nanoparticles (MGCN) against fluconazole-resistant Candida albicans.Materials and Methods: A novel formulation of MGCN was prepared and characterized to determine their size, shape and polydispersity index. Moreover, the efficacy of fluconazole or MG or MGCN was determined against intracellular C. albicans in macrophages and the systematic candidiasis in a murine model. The safety of MG or MGCN was tested in mice by analyzing the levels of hepatic and renal toxicity parameters.Results: Candida albicans did not respond to fluconazole, even at the highest dose of 20 mg/kg, whereas MG and MGCN effectively eliminated C. albicans from the macrophages and infected mice. Mice in the group treated with MGCN at a dose of 10 mg/kg exhibited a 90% survival rate and showed the lowest fungal load in the kidney, whereas the mice treated with free MG at the same dose exhibited 50% survival rate. Moreover, the administration of MG or MGCN did not induce any liver and kidney toxicity in the treated mice.Conclusion: The findings of the present work suggest that MGCN may be proved a promising therapeutic formulation to treat azole-resistant C. albicans infections.Keywords: chitosan nanoparticles, fluconazole-resistant, systemic Candidiasis, methylglyoxal